Stochastic Comparisons of Residual Entropy of Order Statistics and Some Characterization Results - Ramesh C. Gupta; H.C. Taneja; Richa Thapliyal (Journal of Statistical Theory and Applications (JSTA), 2014)
In this paper, we have presented some results for the residual and past entropies of order statistics. Results on the stochastic comparisons based on residual entropy of order statistics are presented. Characterization results for these dynamic entropies based on the sufficient condition for the uniqueness of the solution of an initial value problem have been considered.